Perempuan di Bidang Politik dalam Surat Kabar Lombok Post Tahun 2019: Analisis Wacana Kritis Perspektif Teun A. Van Dijk - Baiq Fahriatin Bakri; Johan Mahyudi; Mahsun Mahsun (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study focuses on the analysis of critical discourse on microstructure, superstructure, and macrostructure in women's text in the political field in the Lombok Post newspaper in 2019. The theory used in this study is the theory of critical discourse analysis according to Teun A. van Dijk on the text dimension which consists of microstructures related to linguistic aspects consisting of semantic, syntactic, stylistic, and rhetorical elements. Superstructures related to the structure of the text or the text scheme. Macrostructure related to the theme in general. This research is qualitative research. Data collection methods in this study use the method of literature, which is a method that can help researchers in collecting data and filtering data that will be used for research. The data analysis method in this research uses the data analysis method according to Miles and Huberman. The results of this study show how the text analysis of news texts about women in politics in the Lombok Post newspaper in 2019 is based on van Dijk's discourse analysis theory.